Analisis Strategi Pemasaran Dan Pengembangan Terhadap Kepuasan Konsumen Pada UMKM Classic Cafe Di Desa Sumberkembar Kecamatan Binangun Kabupaten Blitar. - An-nisaa Kristianti; Siswahyudianto Siswahyudianto (STIE AMKOP, 2023)
Mini classic cafe is one of the efforts engaged in the cafe field. A cafe with a classic concept so comfortable to just hang out relax with friends. This study aims to find out and analyze marketing strategies and development strategies in improving sales turnover of classic cafe. Competition in binangun district is getting tighter because so many innovative new cafe has emerged that every entrepreneur must better understand the aspect of improving their business competitiveness of the methods used in this study is a descriptive qualitative approach for data collection techniques with interviews and documentation. Keywords: Marketing Strategy, Consumer Satisfaction, UMKM